The Impact of Information Infrastructure Capabilities on Knowledge Manipulation Skills: A Conceptual Framework - Lew Sook, Ling; Uchenna C., Eze (2008)
The globalisation of business, the growing use of information and communications technology (ICT) and, the shift from production-based to knowledge-based economy have given knowledge management (KM) a critical position across firms. However, there is limited empirical link between KM and information infrastructure capabilities [IICs] [1, 2]. A key objective of this paper, therefore, is to determine the impact of information infrastructure capabilities on knowledge manipulation skills. This study will also examine specific applications that enable KM activities in firms. We will collect data from a sample of about 600 firms in MSC using questionnaires. Multiple analytical tools will be used in this study to determine the significant levels of associations and interactions between the variables. This research would provide useful information that could help MSC companies determine types of information infrastructures for effective KM implementation. To academics, the empirical insights from this study would be useful for theory building in the subject area.